Activation-Induced Cytidine Deaminase Does Not Impact Murine Meiotic Recombination - Cortesao, C. S. (2013)
Activation-Induced Cytidine Deaminase (AID) was first described as the triggering enzyme of the B-cell-specific reactions that edit the immunoglobulin genes, namely somatic hypermutation, gene conversion and class switch recombination. Over the years, AID was also detected in cells other than lymphocytes, and it has been assigned additional roles in the innate defense against transforming retroviruses, in retrotransposition restriction and in DNA demethylation. Notably, AID expression was found in germline tissues, and in heterologous systems it can induce the double-strand breaks required for the initiation of meiotic recombination and proper gamete formation. However, since AID deficient mice are fully fertile, the molecule is not essential for meiosis. Thus, the remaining question that we addressed here is whether AID influences the frequency of meiotic recombination in mice. We measured the recombination events in the meiosis of male and female mice F1 hybrids of C57BL/6J and BALB/c, in Aicda(+/+) and Aicda(-/-) background using a panel of SNPs that distinguishes C57BL/6J from BALB/c genome across the 19 autosomes. In agreement with the literature, we found that the frequency of recombination in the female germline was higher than in male germline, both in the Aicda(+/+) and the Aicda(-/-) backgrounds. No statistical difference was found in the average recombination events between Aicda(+/+) and Aicda(-/-) animals, either in females or males. In addition, the recombination frequency between SNPs flanking the IgH and Igκ loci was also not different. We conclude that AID has a minor impact, if any, on the overall frequency of meiotic recombination.